2020
DOI: 10.1161/jaha.119.014140
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Serum Sodium is Associated With Increased Mortality Among Unselected Cardiac Intensive Care Unit Patients

Abstract: Background Abnormal serum sodium levels have been associated with higher mortality among patients with acute coronary syndromes and heart failure. We sought to describe the association between sodium levels and mortality among unselected cardiac intensive care unit ( CICU ) patients. Methods and Results We retrospectively reviewed consecutive adult patients admitted to our cardiac in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…A recently published study confirmed that the relationship between sodium at admission and mortality in cardiac intensive care units and in hospital was a J-shaped curve. Patients with hypernatremia were those with the high risk of adverse outcomes, more severely burdened with comorbidities, and with increased adjusted mortality after discharge [14]. The authors of this study associated the results obtained with the possible negative impact of hypernatremia on left ventricular systolic performance, insulin sensitivity, or nerve and muscle function, because such correlations had been described in the literature, but also took into account the likelihood of the worsening prognosis of comorbidities that increase the possibility of elevated sodium levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published study confirmed that the relationship between sodium at admission and mortality in cardiac intensive care units and in hospital was a J-shaped curve. Patients with hypernatremia were those with the high risk of adverse outcomes, more severely burdened with comorbidities, and with increased adjusted mortality after discharge [14]. The authors of this study associated the results obtained with the possible negative impact of hypernatremia on left ventricular systolic performance, insulin sensitivity, or nerve and muscle function, because such correlations had been described in the literature, but also took into account the likelihood of the worsening prognosis of comorbidities that increase the possibility of elevated sodium levels.…”
Section: Discussionmentioning
confidence: 99%
“…A sodium concentration within the range of 135-145 mmol/ L is treated as normal. Although in the general population, combined sodium and water deficits are far more frequent than isolated deficits of either constituent, in patients who cannot respond to thirst by the voluntary ingestion of fluids, or in those with an inadequate thirst response (like in many geriatric patients), relatively pure water depletion (dehydration) leading to hypernatremia is observed [13,14]. Hypernatremia outcomes observed in older people are in parallel to those described for dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…The association between dysnatremia and increased short and long-term mortality was previously reported by several investigators. 5,9,14,15,17 Both decrease and increase in discharge serum sodium from the optimal range were associated with increased 1-year mortality, as shown in the U-shape mortality curve. We observed that any degree of deviation of discharge serum sodium from the optimal range was associated with increased 1-year mortality, even if the deviation was minimal.…”
Section: Ta B L Ementioning
confidence: 93%
“…3,4 Dysnatremia is the most common electrolyte disorder affecting 14%-25% of all hospitalized patients. [5][6][7][8][9][10] The incidence of dysnatremia may vary in specific populations; for example, it is reported to be lower in non-medical patients and higher in heart failure patients. 11,12 Even though the presence of hyponatremia is more common than hypernatremia, a recent study reported an increase in the incidence of hypernatremia in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies on the association of hypochloremia and mortality were presented at the American College of Cardiology in March 2020. One study found that hypochloremia was a strong independent predictor of mortality and that an abnormal serum chloride on admission is associated with increased short-and long-term mortality [25]. A study of 289 patients undergoing left ventricular assist device placement found that hypochloremia was associated with decreased survival at 1 year [26].…”
Section: Clinical Trials -Chloride In Chronic Hfmentioning
confidence: 99%